Eksistensi Asas Monogami Dan Praktik Poligami Dalam Perpektif Politik Hukum - Suriyadi, Suriyadi; Alamudi, Ichwan Ahnaz (Jayapangus Press, 2025)
Law Number 1 of 1974 on Marriage explicitly adheres to the principle of monogamy as stated in Article 3 paragraph (1). However, paragraph (2) of the same article provides an exception by allowing polygamy under certain conditions, raising the impression of normative inconsistency. This research focuses on analyzing the existence of the monogamy principle in relation to the practice of polygamy from the perspective of legal politics. The study employs a normative juridical method with statutory, conceptual, and historical approaches. The findings indicate that, from a legal standpoint, polygamy is not entirely contradictory to the monogamy principle as long as it complies with legal requirements, namely: (1) the wife is unable to fulfill her marital duties, (2) the wife suffers from a physical disability or incurable disease, or (3) the wife is unable to bear children. Beyond these conditions, polygamy is not justified and is considered contrary to the principle of monogamy. From a legal-political perspective, monogamy remains the primary principle, while polygamy is recognized only as a limited exception. Furthermore, in the Civil Code, monogamy is absolute, and violations may be subject to criminal sanctions under Article 279 of the Indonesian Penal Code. Thus, polygamy practiced outside the legal framework may be deemed a violation of the monogamy principle.